2020
DOI: 10.1111/cns.13401
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Brain‐gut‐microbiota Axis in increased intestinal permeability induced by central nervous system injury

Abstract: Central nervous system injuries may lead to the disorders of the hypothalamic‐pituitary‐adrenal axis, autonomic nervous system, and enteric nervous system. These effects then cause the changes in the intestinal microenvironment, such as a disordered intestinal immune system as well as alterations of intestinal bacteria. Ultimately, this leads to an increase in intestinal permeability. Inflammatory factors produced by the interactions between intestinal neurons and immune cells as well as the secretions and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 68 publications
1
56
0
Order By: Relevance
“…Moreover, it has been hypothesized that gut dysbiosis may be a cause of increased levels of oxidative stress in the central nervous system [85]. But also vice versa, central nervous system injuries may cause changes in the gut environment, and trigger alterations of gut microbiome [86]. In this context, it has been demonstrated that brain injury may induce changes in the gut microbiome composition via altered autonomic balance [24].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been hypothesized that gut dysbiosis may be a cause of increased levels of oxidative stress in the central nervous system [85]. But also vice versa, central nervous system injuries may cause changes in the gut environment, and trigger alterations of gut microbiome [86]. In this context, it has been demonstrated that brain injury may induce changes in the gut microbiome composition via altered autonomic balance [24].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been hypothesized that gut dysbiosis may be a cause of increased levels of oxidative stress in the central nervous system 79 . But also vice versa, central nervous system injuries may cause changes in the gut environment, and trigger alterations of gut microbiome 80 . In this context, it has been demonstrated that brain injury may induce changes in the gut microbiome composition via altered autonomic balance 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Reversely, in a global study (COPDMAP study) scientists reported that respiratory infections impact upon the intestinal microbiome mediated by Th17 cells ( Wang and on behalf of COPDMAP study, 2017 ). Recently, it is shown that this bidirectional dialogue is not only of concern to the bacterial potential but it is related to fungal one as well ( Li X. et al., 2020 ). The role of resident intestinal macrophages in airway inflammation and fungal dysbiosis is highlighted ( Leonardi et al., 2018 ).…”
Section: The Gut–lung Microbiome Axismentioning
confidence: 99%